Vocabulary Learning Strategies of Indonesian EFL Learners in Malaysia: A Focus on Gender - Ridwan Muhammad Nur; Zailani Binti Jusoh (International Journal of English and Applied Linguistics (IJEAL), 2022)
Vocabulary learning is vital for EFL students. Students face difficulties in learning new English vocabulary. Meanwhile, few studies have investigated the strategies used by Indonesian English as a Foreign Language (EFL) learners to learn new words and the relationship with their gender differences. And there need to be more studies that examine the vocabulary learning strategies (VLSs) of Indonesian students studying abroad in the ESL context. Considering the increasing number of Indonesian students studying in ESL communities, this study aims to identify the vocabulary learning strategies employed by Indonesian university students who are pursuing their studies at universities in Malaysia. There were 183 students (89 males and 94 females) enrolled in various degree programmes randomly selected in this study. The Vocabulary Learning Strategies Questionnaire from(Almabrouk, 2017),  based on (Schmitt, 1997)’s taxonomy, was adopted as the data collection instrument. The findings showed that the most frequent strategy employed by the respondents was 'trying to develop vocabulary knowledge by watching English TV channels (e.g. movies, songs, documentaries from the metacognitive category. Meanwhile, the least frequent strategy employed by the respondents was 'ask the lecturer for translation of the new word into an L1 translation' from the social category. The results also indicated that there were no statistically significant differences in the use of VLSs based on gender.